School Social Workers’ Roles Involving Teacher-StudentSexual Misconduct and Exploitation (International Journal of Scientific Research and Management (IJSRM), 2025)
Incidents of sexual misconduct by educators continue to become more prevalent in the United States, resulting in negative social, emotional, and psychological effects on many students. School social workers are professionals with backgrounds in prevention, intervention, and advocacy; however, very little literature has examined the roles of school social workers in preventing and addressing teacher-student sexual misconduct. This case study explored school social workers’ roles and their perceptions thereof in relation to incidents that involved teacher-student sexual misconduct and exploitation. General systems theory provided the framework for understanding the roles of social workers and their approaches to working with the different systems associated and connected with the entire education system, including teachers and students. Nine school social workers participated in 30-45 minute audiotaped, in-depth, face-to-face interviews and provided data for this study related to their roles and responsibilities in addressing sexual misconduct in schools. Transcribed interviews were coded, first using emergent open coding and then using focused/axial coding, to form 2 main themes. School social workers in this district were identified as having no well-defined primary or secondary roles related to prevention of and response to teacher-student sexual misconduct, which was reported to result from a number of barriers to school social workers’ ability to deliver effective services. A reevaluation of school social workers’ roles to include addressing crises such as sexual misconduct has the potential to promote positive social change by improving the educational system and the school’s ability to provide a healthier educational environment for students.